World war I day by day - Hook, A. ([S.l.] : Imprint unknown, 2004)
The causes of the (3z(Bwar to end all wars(3y (Bhave been debated exhaustively over the years since Archduke Franz Ferdinand and his wife were assassinated on June 28, 1914. Whatever the precise reasons for the rush to war caused by this act of terrorism, the conflict itself sounded the death knell of the great powers that fought it. Caused by the expansionist policies of the Old World empires, World War I ended in 1918 only after the Central Powers had been crushed following the entry of United States troops onto the battlefield. The war itself was characterised by long periods of attrition. After the initial assaults, each of the fronts settled into a bloodbath of butchery that gave staggering casualty levels. Estimates suggest that nearly ten million soldiers were killed and at least twenty million wounded. Civilians, too, suffered to an unparalleled extent-- around two million Russians died, along with 500,000 Germans, and 600,000 Armenians. A truly global conflict-- it was fought in Europe on Balkan, Eastern, Italian and Western fronts, in Africa and the Middle East, in Turkey and Mesopotamia; on land, at sea, and in the air. It was also a war that saw many military innovations including the major use of gas, the first intensive aerial bombing attacks, the advent of tanks onto the battlefield, and protracted submarine warfare. With over 350 illustrations, World War I Day by Day provides a substantial reference to the day-by-day conduct of all facets of the war-- including politics, the battles and campaigns in every theatre, innovations in land, sea and aerial warfare, and other major events.s
Keywords: World War (1914-1918)